Case Report: Diverse cardiac and muscular phenotypes in DES c.1024A>G (p.Asn342Asp) variant: a case series with limb weakness as the initial presentation - Wang, Liuyang; Yue, Dongyue; Chen, Zijun (Frontiers in Cardiovascular Medicine, 2025)
We report three patients with bilateral lower limb weakness as the initial symptom. Case 1 presented at 37 years old with bilateral lower limb weakness. The condition gradually worsened, eventually leading to wheelchair dependence. He later sought medical attention for heart failure. Echocardiography showed diffuse left ventricular dysfunction, and the electrocardiogram revealed third-degree atrioventricular block. Case 2 developed bilateral lower limb weakness at 38 years old, with milder symptoms. The main cardiac manifestation was paroxysmal atrial fibrillation. Case 3 presented at 33 years old with lower limb weakness and myalgia, with significant involvement of all four limbs. The primary cardiac finding was left ventricular hypertrophy, and the electrocardiogram showed sinus pauses. Despite the differences in clinical presentations, all three patients were diagnosed with the same DES c.1024A>G (p.Asn342Asp) variant. We discuss the possible factors contributing to the phenotypic differences. Based on the uniqueness of this pathogenic variant site, we propose recommendations for the treatment and management of desminopathy.